DIVIDEND AND NON-DIVIDEND FACTORS EFFECT ON STOCK PRICE IN THE INDONESIAN STATE OWNED BANK: PT. BANK NEGARA INDONESIA SHARE PRICES PERIOD 2007-2018 - Abiazka, Hifzhan; Nugroho, Anggoro Budi (Journal of Business and Management, 2018)
Abstract.Indonesia has experienced significant growth with the major development of infrastructure under the new government’s policy of Nawacita. This has opened the door for the growth of a number of critical sectors, one of which is the banking industry. The growth of the banking sector has been shown by the increase in its stock prices. BNI share prices had been on the rise in the past decade. However, BNI share prices began to fall into a bearish trend from March until September 2015. It is from this crucial period that the researcher would like to study the effect of dividend pay-out towards the stock price of BNI, as well as other non-dividend factors that may contribute to the price of stock, those factors being ROE, EPS, NIM, NPL Gross, NPL Nett, LDR, and BOPO. This research uses annual data of BNI dividend pay-out with monthly data of BNI share price that span from 2013 to 2018. As for non-dividend factors with share price, both variables uses BNI quarterly data from 2007 to 2017. The results shows that NIM and NPL Gross have a negative impact on stock price, while only LDR showed a positive impact. Dividend also showed a strong correlation with stock price. These results indicate that dividend is a highly considered factor for investors, as opposed to its financial performance in the financial reports. Therefore, based on the results, BNI and its investors should consider the dividend pay-out as it can impact the stock price.Keywords: Bank, Stock price, Dividend, Non-Dividend factors, Correlation.